Constraints on the Northwestern Atlantic Deep Water Circulation From Pa-231/Th-230 During the Last 30,000 Years - Suefke, Finn; Poeppelmeier, Frerk; Goepfert, Tyler Jay; Regelous, Marcel; Koutsodendris, Andreas; Blaser, Patrick; Gutjahr, Marcus; Lippold, Joerg (Paleoceanography and Paleoclimatology, 2019)
Global climatic changes during the last glacial and deglacial have been related to variations of the Atlantic Meridional Overturning Circulation (AMOC). Here, we present new and refined Pa-231/Th-230 down-core profiles extending back to 30 ka BP from the northwestern Atlantic along the Atlantic Deep Western Boundary Current, which is the main component of the southward deep backflow of the AMOC. Besides the well-known Bermuda Rise records, available high-resolution Pa-231/Th-230 data in the northwestern Atlantic are still sparse. Our new records along with reconstructions of deep water provenance from Nd isotopes constrain the timing and magnitude of past changes in AMOC from an additional northwestern Atlantic region forming a depth transect between 3,000- and 4,760-m water depth. Our extended and improved data set confirms the weakening of the AMOC during deglacial cold spells such as Heinrich Event 1 and the Younger Dryas interrupted by a reinvigoration during the Bolling-Allerod interstadial as seen in the prominent Pa-231/Th-230 records from the Bermuda Rise. However, in contrast to the Bermuda Rise records, we find a clearly reduced circulation strength during the Last Glacial Maximum in the deep Atlantic.
CRIS-Team WoS Importer:2019-12-17